2013
DOI: 10.1371/journal.pone.0061215
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of Mercury in Earthworms and the Effect of Mercury on the Associated Bacterial Communities

Abstract: Methylmercury compounds are very toxic for most organisms. Here, we investigated the potential of earthworms to methylate inorganic-Hg. We hypothesized that the anaerobic and nutrient-rich conditions in the digestive tracts of earthworm's promote the methylation of Hg through the action of their gut bacteria. Earthworms were either grown in sterile soils treated with an inorganic (HgCl2) or organic (CH3HgCl) Hg source, or were left untreated. After 30 days of incubation, the total-Hg and methyl-Hg concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 65 publications
2
20
0
Order By: Relevance
“…Earthworms (Eisenia foetida) were found to potentially methylate Hg in their digestive tract (Hinton and Veiga, 2002). In addition, earthworms (Lumbricus terrestris) showed MeHg synthesis in vivo due to the sulfatereducing bacteria found in earthworms but not in soils (Rieder et al, 2013). In our study, MeHg concentrations in the forest soil and native B. parvus earthworms were expected to increase due to the higher soil THg concentrations in the leachate-contaminated forest sites compared to the reference sites.…”
Section: Mercury Methylation Characteristicsmentioning
confidence: 68%
See 1 more Smart Citation
“…Earthworms (Eisenia foetida) were found to potentially methylate Hg in their digestive tract (Hinton and Veiga, 2002). In addition, earthworms (Lumbricus terrestris) showed MeHg synthesis in vivo due to the sulfatereducing bacteria found in earthworms but not in soils (Rieder et al, 2013). In our study, MeHg concentrations in the forest soil and native B. parvus earthworms were expected to increase due to the higher soil THg concentrations in the leachate-contaminated forest sites compared to the reference sites.…”
Section: Mercury Methylation Characteristicsmentioning
confidence: 68%
“…It has been generally accepted that inorganic forms of Hg can be methylated by soil bacterial activity (mostly under anaerobic conditions); methylation enhances bioavailability and bio-toxicity and increases potential threats to soil ecosystem functions (Shao et al, 2012). However, recent studies have found that inorganic Hg is methylated within the guts of earthworms and not by soil bacterial action, based on the fact that sulfate-reducing bacteria were detected in the gut tract of earthworms (Kaschak et al, 2014;Rieder et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Other soil properties, such as texture, or redox conditions, may also be important factors. Furthermore, earthworms may vary within and between species in their capacity to methylate inorganic Hg in their digestive systems , and these differences may be producing the high levels of variation that were observed (although we note that the earthworm communities were similar at different sites). The present study is unable to answer questions about in vivo methylation processes in earthworms, and this issue should be a priority research direction in the future.…”
Section: Discussionmentioning
confidence: 79%
“…(2014) In vitro incubation of gut inhabiting bacteria of the earthworm Lumbricus terrestris treated with HgCl 2 or CH 3 HgCl in sterile and non-sterile soils Rieder et al (2013) In vitro incubation of intestinal microbiota of the earthworm Eisenia foetida and intestinal sulfate reducing-bacteria in pure cultures with HgCl 2 in sterile and non-sterile soils time. They are based on the MeHg extraction by the Westöö method and the identification of the cyanide and iodide salts by thin-layer chromatography (TLC) which involve many limitations for a correct isolation and determination of MeHg.…”
Section: Cow and Sheep Rumenmentioning
confidence: 99%
“…Hence, these results cannot confirm that methylation takes place in the guts so that further experiments in this field should be performed. Rieder et al (2013) conducted a very interesting study with natural soils but sterilized, so it was possible to discriminate MeHg produced in the soil or in the earthworm gut. They performed two independent experiments with the earthworm Lumbricus terrestris and sterile soils.…”
Section: Earthwormsmentioning
confidence: 99%